Initial Preparation in Teaching Indonesian Language at Islamic Elementary School Grade 3 - Nuroh, Ermawati Zulikhatin; Fisabilillah, Frida (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the pivotal role of early learning activities in Indonesian language instruction by examining teacher perception strategies. Employing a descriptive qualitative research methodology, data were collected through student interviews, observation, and documentation at Permata Sunnah Islamic School. Findings revealed three primary perception activities utilized by teachers: questioning, practical materials utilization, and video presentation. These activities facilitate mental preparedness and foster students' receptivity to new information, thereby enhancing the efficacy of early learning in Indonesian instruction. This study underscores the importance of varied perceptual approaches in pedagogical practices and provides valuable insights for educators seeking to optimize early learning experiences in language instruction. Highlights : Varied perceptual approaches enhance early learning outcomes. Teacher questioning, practical materials, and video presentation are pivotal in Indonesian instruction. Qualitative research provides insights into effective pedagogical strategies for language learning. Keywords: Early learning, Teacher perception, Indonesian instruction, Qualitative research, Pedagogical practices